2022
DOI: 10.1016/j.acap.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Use of Social Media as a Health Information Source for Their Children: A Scoping Review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 59 publications
(350 reference statements)
2
37
0
Order By: Relevance
“…Surveys of parents have also shown that reasons for vaccine hesitancy included concerns about unknown longer-term and serious side effects of the vaccine [21] . Parental concerns could also be attributable to the widespread use of social media as a source of information by parents, with misinformation and anti-vaccine sentiments often being reported in social media [22] , [23] . As well, the lower vaccination rate could also be explained by pediatricians not frequently asking about vaccination status or engaging in vaccine counselling during all or most office visits, which serve as opportunities to increase vaccine confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of parents have also shown that reasons for vaccine hesitancy included concerns about unknown longer-term and serious side effects of the vaccine [21] . Parental concerns could also be attributable to the widespread use of social media as a source of information by parents, with misinformation and anti-vaccine sentiments often being reported in social media [22] , [23] . As well, the lower vaccination rate could also be explained by pediatricians not frequently asking about vaccination status or engaging in vaccine counselling during all or most office visits, which serve as opportunities to increase vaccine confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, professional guidance is urgently needed after obtaining a diagnosis of the disease. In recent years, social media has become a source of health information for parents ( 28 ). However, confusion and misunderstanding among parents appeared with the application of professional vocabulary and the complexity of information ( 29 , 30 ), in consequence, healthcare professionals were asked to verify the information on social media ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, teenagers use internet media for learning, specifically in urban areas, and access to information is high. [17][18][19][20] Attitudes in dengue control are directly influenced by the variable perception of the need for digital technology and program benefits. This is related to the source of information obtained through digital media.…”
Section: Discussionmentioning
confidence: 99%